Digital Gold or Worthless Bytes? An Exploration of Bitcoin Price Fluctuations and Assessment of Event Driven Volatility - Manning Smith, James (2015)
The value of Bitcoin has been witnessed to extreme fluctuations over the last two and a half years. With a seriously volatile history, Bitcoin’s credibility as a currency has been questioned, and along with its widespread use for criminal activity online, its place in business and finance has come under fire. This dissertation sets out to explore these aspects of the Bitcoin economy, along the way, examining a number of other factors that have been said to influence Bitcoin value. Using Google Trend Data, periods in which interest in Bitcoin increased has been used to identify events surrounding the Bitcoin economy. Events coded as raising general awareness of Bitcoin, the opening and closing of illicit market, security issues and foreign regulation, were tested to measure their impact on Bitcoin value, intra-day volatility and inter-day price changes. It was found that, despite evidence to suggest the contrary, illicit markets did not largely affect Bitcoin value and that Bitcoin gained value as media coverage increased. It is concluded that Bitcoin is largely influenced by awareness, but that this awareness caused over valuation. Recommendations to businesses and future research suggestions are made based on the evidence found through this research.